(untitled) (Journal of Medical Sciences, 2023)
Introduction: Smoking is the worst human behavior; it is practiced by people addicted to nicotine. Cigarettes contain many harmful compounds, some of them implicated in different types of cancer. The effect of cigarette smoking can be shown in the disturbance of many biochemical and hematological processes detected by laboratory investigations. The aim of the present study is to evaluate the effect of cigarettes smoking on complete blood count (CBC) and liver function enzymes in smokers in city of Brack in southern Libya. Materials and Methods: One hundred healthy males were volunteers to participate in the study. They were divided into two groups, 50 nonsmokers used as a control group, the other fifty were smokers. 5 ml of blood were withdrawn for the estimation of serum liver function enzymes; (alkaline phosphatase (ALP), alanine aminotransferase (ALT) and aspartate aminotransferase (AST) and CBC. Questionnaire and a consent form were used to collect general information. Results: The result showed significant (P˂0.000) increase in the activity of liver enzyme ALP, AST, AST in smokers compared to control group. Whereas ALT was significantly increased in smokers for more than ten years compared to those who smoked for less than ten years. A significant (P˂0.001) increase found in MCV and WBC counts in smokers compared to control group. Conclusion: cigarette smoking affected liver function detected by alterations in the activity of liver function enzymes and the change was dependent on smoking duration. Some blood count investigations were also changed.